P33 Iron deficiency independently predicts survival in idiopathic pulmonary arterial hypertension. (16th November 2010) - Rhodes, CJ; Howard, LS; Busbridge, M; Ashby, D; Kondili, E; Gibbs, JSR; Wharton, J; Wilkins, MR
Abstract : Objectives: Characterise the iron status of patients with idiopathic pulmonary arterial hypertension (IPAH) and its clinical importance. Methods: Circulating markers of iron status and erythropoiesis were determined in 135 patients with IPAH and correlated with clinical indices and survival. Results: Iron deficiency, defined by raised plasma soluble transferrin receptor (sTfR) levels (>28.1 nmol/l) was present in ∼63% of patients with IPAH. Iron, ferritin and transferrin saturation levels were also reduced (Abstract P33 Figure 1 ); whereas mean haematocrit and haemoglobin levels were similar to healthy controls and red cell distribution width was increased. Levels of the master iron regulator hepcidin, which inhibits the dietary uptake and decreases serum iron, were raised (50.5 vs 34.4±3.0 ng/ml; p=0.04) despite the presence of iron deficiency in the majority of patients. Hepcidin correlated inversely with sTfR and erythropoietin (EPO) levels as would be expected, but not with IL-6, the most important inflammatory stimulus for hepcidin expression. After adjusting for iron status, hepcidin levels were significantly higher in IPAH compared with healthy controls (p=0.001). Plasma sTfR levels increased with WHO class (p<0.05), showed a weak but significant correlation with 6MWD (R=−0.25, p=0.03) and growth differentiation factor-15 (R=0.281, p=0.01) and independently predicted survival after adjustments for 6MWD, WHO class and NT pro-BNP levels (p=0.022). Conclusions: A significant proportion of IPAH patients are iron deficient and this relates to disease severity and outcome. Hepcidin levels are inappropriately high in IPAH and may be driving iron deficiency.